Pediatric Teleradiology in Low-Income Settings and the Areas for Future Research in Teleradiology - Andronikou, Savvas (Frontiers in Public Health, 2014)
Teleradiology is an established mechanism to overcome the lack of on-site radiologists and can benefit children in developing countries. In this ‘perspective’ on tele-radiology for pediatric care in underdeveloped countries, three low cost tele-radiology programs are discussed from experiences of one tele-radiologist, in relation to previous publications on this subject. Key issues discussed include mechanisms for sustainability, cost-effectiveness, resources and barriers to success. Reliance on each link of a tele-reading chain is highlighted as a constant source for concern.